THE FORMATION OF STUDENTS' SOCIAL COMPETENCES IN A TECHNICAL UNIVERSITY AS A MULTILEVEL EDUCATIONAL COMPLEX - Svetlana V. Sergeyeva; Olga A. Voskrekasenko (National Research Mordova State University, 2016)
Introduction: the article deals with the problem of expanding students' competencies. A modern technical University must train professionals who apart from having a high special competence, also have the understanding of the common cultural issues. The solution of the problem is possible through a specially organized activity in the system of lifelong education. The formation of students' social competences assumes a particular relevance, in the educational process, of a technical university as a multilevel educational complex in the context of the implementation of competence-based approach. Materials and Methods: the authors use the following methods of scientific research: system-structural analysis, synthesis, working with literature, summarizing the e xperience, and critical reflection. Results: the article presents a programme "The Formation of Students' Social Competences in a Technical University as a Multilevel Educational Complex" developed by the authors. The content of the programme suggests the formation of social competence of health preservation, civic consciousness, communication and social interaction as well as the formation of competence in th e field of information technology. Discussion and Conclusions: the programme developed by the authors is one of the results of research carried out in the work of the Russian Academy of Education experimental unit, case study of Penza State Technological University. The main target of this programme is to promote engineering staff training for a regional labour market. This programme can be used in dif ferent institutions of continuing education.